Validation of the accident and emergency experience questionnaire: a cross-sectional survey - Eliza Lai-Yi Wong; Annie Wai-Ling Cheung; Hong Qiu; Jonathan Chun-Hei Ma; Eng-Kiong Yeoh (BMC Health Services Research, 2023)
Abstract Background Patient feedback is an important way for healthcare providers to understand patient experience and improve the quality of care effectively and facilitate patient-centered care in the healthcare system. This study aimed to suggest a validated instrument by evaluating the psychometric properties of the Accident and Emergency Experience Questionnaire (AEEQ) for measuring patient experience in the accident and emergency department (AED) service among the adult Chinese population. Methods Attendances aged 18 or above from all public hospitals with AEDs during 16–30 June 2016 were targeted and a cross-sectional telephone survey was conducted using AEEQ. Preliminary AEEQ consisted of 92 items, including 53 core evaluative items and 19 informative items, and the other 20 items covered socio-demographics, self-perceived health status, and free open-ended comments on AED service. Psychometric properties of the evaluative items were evaluated for practicability, content and structure validity, internal consistency, and test-retest reliability in this study. Results A total of 512 patients were recruited with a response rate of 54% and a mean age of 53.2 years old. The exploratory factor analysis suggested removing 7 items due to weak factor loadings and high cross-loading and then leaving 46 items grouped into 5 dimensions, which were care and treatment (14 items), environment and facilities (16 items), information on medication and danger signals (5 items), clinical investigation (3 items), and overall impression (8 items) to represent patient experience on AED service. The internal consistency and test-retest reliability were high with Cronbach’s alpha coefficient and Spearman’s correlation coefficient of the suggested scale of 0.845 and 0.838, respectively. Conclusion The AEEQ is a valid and reliable instrument to evaluate the AED service which helps to build the engagement platform for promoting patient-centered care between patients and frontline healthcare professionals and improving healthcare quality in the future.